PENGARUH REKRUTMEN APARATUR SIPIL NEGARA TERHADAP PENYELENGGARAAN PELAYANAN PUBLIK (Studi di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Halmahera Utara) - HARIAWAN, SHINTIA; KIYAI, BURHANUDDIN\; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to determine and analyze the Effect of Recruitment on the Implementation of Public Servicesin the Population and Civil Registration Office of North Halmahera Regency. The research method that I usein this research is quantitative research methods. Data and information were collected through a questionnairetechnique and completed with interview data source techniques / research respondents were all employees inthe Department of Population and Civil Registration of North Halmahera Regency as many as 36 people.Theanalysis techniques used by testing hypotheses are frequency tables, product moment correlations and simplelinear regression. Based on the description of the data it turns out that most of the respondents who gave anassessment of the recruitment variable of the State Civil Apparatus were in the category of â€œhighâ€ or at 66,66%,then as many as 12 employee respondents or at 33,33% who state that the recruitment of the State CivilApparatus in the Office Population and Civil Registration of Nort Hamlmahera Regency are in the â€œmediumâ€category, while the category of â€œlawâ€ is not out of 36 employee respondents who were interviewed in the NorthHalmahera Regency Population and Civil Registration Service. While public service variable in the NorthHalmahera Regency Population and Service are in the â€œhighâ€ category or 52,77%, then 17 employeerespondents or 47,22% stated thah public services in the Halmahera Regency Population and Civil RegistrationService in the â€œmediumâ€ category, while in the â€œlowâ€ category there isnâ€™t.Keywords: Recruitment of State Civil Apparatus, Public Services